THE IMAGE OF A TEENAGER IN CINEMATOGRAPHY AND LITERARY ADAPTATIONS (The Conference Hub, 2025)
This article explores the evolving image of the teenager in cinematography, particularly in films adapted from literary works. It examines how adolescent characters are portrayed visually and narratively, and how these representations differ or align with their original literary sources. Drawing on examples from classic and contemporary adaptations—including works based on novels by J.D. Salinger, Suzanne Collins, and Stephen Chbosky—the study analyzes the transformation of character identity, emotional expression, and psychological depth when adapted for the screen. Emphasis is placed on the cinematic tools used to convey the complexities of adolescence, such as mise-en-scène, cinematography, dialogue, and soundtrack. The research also investigates how cultural, generational, and media-specific elements influence the portrayal of teenage identity in film. Ultimately, the article argues that while literary and cinematic mediums differ in form and focus, both offer valuable and complementary perspectives on the challenges and inner lives of teenagers.